Pembinaan FARMACIL (Farmasis Cilik) di SDN 2 Cakranegara - Candra D. Hamdin; Handa Muliasari (Universitas Mataram, 2019)
The drug is known as a preparation used by humans as a healing medium. The origin of the drug is a toxic compound that can be dangerous when using it. The usage of drugs can be obtained if it is used correctly. Basic knowledge about drugs is very important to know so that the benefits of drugs can be obtained. The Indonesian Pharmacists Association (IAI) has made a simple method to facilitate drug use, by carrying out the national program